Sequencing versus continuous granular sludge reactor for the treatment of freshwater aquaculture effluents. (1st August 2021) - Santorio, Sergio; Couto, Ana T.; Amorim, Catarina L.; Val del Rio, Angeles; Arregui, Luz; Mosquera-Corral, Anuska; Castro, Paula M.L.
Highlights: Granular sludge sequencing & continuous reactors cope with extremely low-strength wastewater. Ammonium and nitrite toxic levels for fish were avoided in both reactors effluent. Ammonium removal up to 100 and 20% in AGS-SBR and CFGR, respectively. AGS-SBR produced a high chemical quality effluent while CFGR treated 6 times higher flows. Biomass in CFGR granulated in 7 days at HRT of 5 min. Abstract: Ammonium and nitrite levels in water are crucial for fish health preservation and growth maintenance in freshwater aquaculture farms, limiting water recirculation. The aim of the present work was the evaluation and comparison of two granular sludge reactors which were operated to treat freshwater aquaculture streams at laboratory-scale: an Aerobic Granular Sludge - Sequencing Batch Reactor (AGS-SBR) and a Continuous Flow Granular Reactor (CFGR). Both units were fed with a synthetic medium mimicking an aquaculture recycling water (1.9–2.9 mg N/L), with low carbon content, and operational temperature varied between 17 and 25 °C. The AGS-SBR, inoculated with mature granules from a full-scale wastewater treatment plant, achieved high carbon and ammonium removal during the 157 operational days. Even at low hydraulic retention time (HRT), varying from 474 to 237 min, ammonium removal efficiencies of approximately 87–100% were observed, with an ammonium removal rate of approximately 14.5 mg NH4 + -N/(L⋅d). Partial biomass washout occurred due to the extremely low carbon and nitrogen concentrations in the feeding, which could only support the growth of a small portion of bacteria, but no major changes on the reactor removal performance were observed. The CFGR was inoculated with activated sludge and operated for 98 days. Biomass granulation occurred in 7 days, improving the settling properties due to a high up-flow velocity of 11 m/h and an applied HRT of 5 min. The reactor presented mature granules after 32 days, achieving an average diameter of 1.9 mm at day 63. The CFGR ammonium removal efficiencies were of approximately 10–20%, with ammonium removal rates of 90.0 mg NH4 + -N/(L⋅d). The main biological processes taking place in the AGS-SBR were nitrification and heterotrophic growth, while in the CFGR the ammonium removal occurred only by heterotrophic assimilation, with the reactor also presenting complete and partial denitrification, which caused nitrite production. Comparing both systems, the CFGR achieved 6 times higher ammonium removal rates than the AGS-SBR, being suitable for treating extremely high flows. On the other hand, the AGS-SBR removed almost 100% of ammonium content in the wastewater, discharging a better quality effluent, less toxic for the fish but treated lower flows. Graphical abstracts: Image, graphical abstract